The role of procurement frameworks in responsible AI innovation in the National Health Service: a multi-stakeholder perspective - Evans, Thomas D.; Ahmad, Omer; Alderman, Joseph E.; Bailey, Georgia; Bannister, Peter; Barlow, Nick; Davison, Natalie; Isaac, Amanda; Kale, Aditya U.; MacDonald, Trystan; Malik, Qasim; Shelmerdine, Susan C.; et al. (Frontiers in Health Services, 2025)
Procurement carries legal requirements across public services in the UK but, for stakeholders in clinical Artificial Intelligence (AI) innovation, it is often poorly understood. This perspective piece summarises insights from a cross-sector workshop exploring the role of procurement frameworks in supporting AI innovation in the National Health Service (NHS). The significant characteristics of AI from a procurement perspective are identified and their consequences are explored. The workshop identified challenges including visibility of AI procurement processes, uncertainty in the value in AI products, process inefficiencies, sustainability and framework design. Opportunities relating to AI procurement were also identified. These insights highlight the potential for procurement frameworks to enable responsible AI innovation in healthcare but acknowledge the need for collaborative efforts from a range of stakeholders to overcome the difficulties experienced by many to date.